A dimensão religiosa e sua influência na recuperação de dependentes químicos: estudo sobre a dependência química no Núcleo de Apoio a Toxicômanos e Alcoolistas (NATA) em Boa Vista, Roraima - Souza, Eldon Mendes de (2015)
The relationship between the religious dimension and its influence on health, more precisely on the recovery process of drug addicts, has been the focus of extensive recently discussion by various theoretical worldwide, as there are several studies that point to the Importance of religiosity in this context. Thus, this work has the main objectives is to identify the importance of the religious dimension (faith and belief) in recovering chemical addiction in the Core support for drug addicts and alcoholics (NATA) in Boa Vista, Roraima. Therefore, we make use of field research and literature, with qualitative and quantitative approach, on the exploratory type, whose source of data collection and analysis was a mixed questionnaire with open and closed questions for users of NATA in Boa Vista-RR. The analysis revealed that the research subjects have aged between 19 and 48 years old, male, single, having secondary education, social middle class, with a variation in occupation ranging from entrepreneur to those who has no work, where the time chemical dependence is extensive, ranging from 1 to 34 years. However, the results showed that regardless of what the religion of these individuals, all believe in God, and therefore believe that religion, as well as religiosity, devotions (acts) and religious symbols, helps in recovery from addiction in various ways. Either by obtaining refuge, the acquiring spiritual knowledge, is the belief that a greater power keep them clean and strong, mainly to keep away from the temptations of drugs. And therefore, practice and devotions using religious symbols, for example, the crucifix, the book of the spirits, the Bible, prayers, hymns, beyond belief and devotion to God to recover, as it helps to relieving pain inflicted by drugs, keeping them vigilant, bringing peace of mind, renewing and strengthening its spirituality. So, that motivates them to practice these actions and use these symbols, it is the faith and belief in doctrine and in God and the achievements, due to feel spiritually renewed and strengthened in the face of drug threats on a daily basis.